ANALYSIS OF CODE-MIXING USAGE IN THE MECHANICAL ENGINEERING COMMUNITY: A SOCIOLINGUISTIC STUDY - Permana, Andi; Sari Dewi, Ika (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2024)
This research aims to investigate code mixing that occurs in the mechanical engineering community. There are two main focuses in this research: the reasons that influence code mixing and the translation techniques used as well as the causes if code mixing is not possible in certain situations. This research method is a qualitative descriptive method with an interactional sociolinguistic approach. Data sources are WhatsApp social media conversation transcripts, post-hoc interviews, and discourse analysis. The research results show that code mixing is carried out by speakers against their interlocutors because they discuss certain topics and quote other people. Participants often use English terms in technical conversations because they are more common and specific than their Indonesian equivalents, so communication becomes smoother and more effective. Apart from that, the use of code mixing is also shaped by the norms and habits formed in a multilingual work environment. The translation methods used by participants are semantic and communicative. This study provides insight into linguistic dynamics within the mechanical engineering community and highlights the importance of understanding the social and linguistic factors that influence communication in professional contexts. This study did not analyze translation effectiveness in detail due to data limitations. Therefore, this research also suggests that the object of further research be expanded to include more translation techniques and more comprehensive discourse analysis